Lithium secondary battery containing perlithium manganese oxide and method for producing same
The lithium secondary battery employing an overlithium manganese oxide with enhanced manganese content and lithium ratio, and optimized charging conditions, effectively addresses the resistance issues associated with oxygen desorption and cation mixing, resulting in improved performance and capacitance characteristics.
Patent Information
- Application Number
- JP2024557786
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-10-13
AI Technical Summary
Lithium secondary batteries with per-lithium-based transition metal oxides face issues with oxygen desorption and cation mixing during high voltage activation, leading to increased positive electrode resistance.
A lithium secondary battery using an overlithium manganese oxide with a manganese content exceeding 50 mol% and a lithium-to-metal ratio exceeding 1, charged to 4.6 V and discharged to 2.0 V, with specific charging and discharging conditions to minimize oxygen desorption and cation mixing.
The battery exhibits improved resistance and output characteristics with minimal increase in positive electrode resistance, achieving excellent capacitance and reduced discharge curve area in the 2.0-3.5V voltage range.
Smart Images

Figure 2025511641000001_ABST
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183648 dated December 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a lithium secondary battery including a lithium-rich manganese-based oxide and a method for manufacturing the same, and more particularly to a lithium secondary battery including a lithium-rich manganese-based oxide having improved resistance characteristics, particularly improved positive electrode resistance characteristics, and a method for manufacturing the same. [Background technology]
[0003] Lithium secondary batteries are energy storage media that have been applied in various fields since they were commercialized in 1991. As the market for products equipped with lithium secondary batteries expands, research into increasing the energy density of lithium secondary batteries is being actively conducted, and one of the most notable methods is the development of a positive electrode active material with a composition that allows the use of a larger amount of lithium than currently available.
[0004] As a positive electrode active material that can utilize more lithium, a perlithium-based transition metal oxide, which has a layered structure and a lithium to transition metal molar ratio of more than 1, has been developed. Lithium secondary batteries using such perlithium-based transition metal oxides can achieve high capacity by performing an activation process at a high voltage of generally 4.4V or more. However, when performing such a high voltage activation process, there is a problem in that oxygen desorption and cation mixing are induced in the crystal structure in the perlithium-based transition metal oxide, greatly increasing the resistance of the positive electrode. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention is for solving the above problems, and aims to provide a lithium secondary battery containing a lithium-rich manganese-based oxide having improved resistance characteristics and a method for manufacturing the same.
Means for Solving the Problems
[0006] On one side, the present invention provides a lithium secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte, which contains a lithium-rich manganese-based oxide in which the content of manganese in the total metal excluding lithium exceeds 50 mol%, and the ratio of the number of moles of lithium to the number of moles of the total metal excluding lithium (Li / Me) exceeds 1. After charging the lithium secondary battery to 4.6 V at 0.1 C, when the total discharge curve area is regarded as 100% in the dQ / dV graph obtained by differentiating the graph of the measured voltage V and the battery discharge capacity Q while discharging to 2.0 V at 0.1 C, the discharge curve area in the voltage range of 2.0 to 3.5 V is 35% or less, preferably 20% to 35%.
[0007] The lithium-rich manganese-based oxide may be represented by the following Chemical Formula 1. [Chemical Formula 1] Li a Ni b Co c Mn d M e O 2 In the above Chemical Formula 1, M contains at least one or more selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, and 1 < a, 0 ≦ b ≦ 0.5, 0 ≦ c ≦ 0.1, 0.5 ≦ d < 1.0, 0 ≦ e ≦ 0.2. Preferably, 1.1 ≦ a ≦ 1.5, 0.1 ≦ b ≦ 0.4, 0 ≦ c ≦ 0.05, 0.5 ≦ d ≦ 0.80, 0 ≦ e ≦ 0.1 may also be satisfied.
[0008] In another aspect, the present invention provides a method for manufacturing a lithium secondary battery, comprising: preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte, the positive electrode including a perlithium manganese-based oxide, in which a manganese content in all metals excluding lithium exceeds 50 mol % and a ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1; activating the battery cell by charging and discharging at least one time, wherein the activating step includes a first charging step of charging the battery cell at a C-rate of less than 0.5 C; and a second charging step of charging the battery cell at a C-rate of 0.5 C or more.
[0009] Preferably, the first charging step may be performed until the SOC of the battery cell reaches 10 to 40, and the second charging step may be performed after the first charging step until the SOC of the battery cell reaches 90 to 150.
[0010] The first and second charging stages may be performed in a constant current mode (CC mode), or the first charging stage may be performed in a constant current mode (CC mode) and the second charging stage may be performed in a constant current-constant voltage mode (CC-CV mode).
[0011] The charge end voltage in the second charging step may be 4.4V or more, for example, 4.4V to 4.8V or 4.5V to 4.8V.
[0012] Preferably, in the present invention, the charging and discharging in the activation step may be performed in a voltage range of 2.0V to 4.6V.
[0013] The lithium secondary battery manufactured through the activation process may have a discharge curve area of 35% or less, preferably 20% to 35%, in a voltage range of 2.0 to 3.5 V, when the total discharge curve area is 100% in a dQ / dV graph obtained by differentiating a graph of voltage V and battery discharge capacity Q measured while charging to 4.6 V at 0.1 C and then discharging to 2.0 V at 0.1 C. Effect of the Invention
[0014] The lithium secondary battery according to the present invention includes a perlithium manganese-based oxide in which the manganese content in all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1. The perlithium manganese-based oxide can be operated at a relatively high voltage compared to lithium nickel-based oxides and has excellent capacity characteristics.
[0015] In addition, the lithium secondary battery according to the present invention suppresses oxygen desorption and cation mixing during the activation process, and reduces Mn ions mixed with cations, resulting in little capacity development, and therefore, when the total discharge curve area in a dQ / dV graph is taken as 100%, the discharge curve area in the voltage range of 2.0 to 3.5 V is shown to be 35% or less, preferably 20% to 35%. The lithium secondary battery according to the present invention having the above-mentioned discharge behavior has little increase in the positive electrode resistance during charging and discharging, and has excellent resistance characteristics and output characteristics.
[0016] In the method for producing a lithium secondary battery according to the present invention, charging is performed at a high C-rate of 0.5 C or more during a part of the activation charging step, thereby forming a Li 2 MnO 3 This allows the cell and positive electrode resistance to be lowered by reducing the activation of the monoclinic phase.
[0017] In addition, since the manufacturing method according to the present invention includes a second charging step in which charging is performed at a higher C-rate than the conventional method, the total time required for the activation process is reduced, thereby improving the production rate of lithium secondary batteries.
[0018] In addition, the manufacturing method according to the present invention performs a first charging step of charging at a low C-rate in the early activation stage, thereby enabling the SEI film to be sufficiently formed on the electrode in the early activation stage. If charging is performed at a high C-rate in the early activation stage, the SEI film may be formed unstably on the electrode, resulting in a decrease in battery life characteristics. [Brief description of the drawings]
[0019] [Figure 1] 2 is a dQ / dV graph of the lithium secondary batteries produced in Examples 1 to 3 and Comparative Example 1. [Diagram 2] 1 is a graph showing the positive electrode resistance of lithium secondary batteries prepared in Examples 1 to 3 and Comparative Example 1, measured by EIS analysis. [Diagram 3] 1 is a graph showing the positive electrode resistance of lithium secondary batteries prepared according to Examples 1 to 3 and Comparative Example 1, measured by DCIR analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The terms and words used in this specification and the claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that an inventor can appropriately define the concepts of terms in order to explain his / her invention in the best possible manner.
[0021] In the present invention, the term "primary particle" refers to a particle unit that does not have grain boundaries when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope. The term "average particle size of primary particles" refers to the arithmetic average value calculated after measuring the particle sizes of primary particles observed in a scanning electron microscope image.
[0022] In the present invention, the "secondary particles" are particles formed by agglomeration of a plurality of primary particles.
[0023] In the present invention, the average particle size D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the particle powder to be measured (e.g., positive electrode active material powder, negative electrode active material powder, etc.). 50can be measured using the laser diffraction method. For example, the powder of the particles to be measured is dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W. A volume cumulative particle size distribution graph is obtained, and the particle size corresponding to 50% of the volume cumulative amount is calculated.
[0024] In the present invention, "SOC X" refers to a state in which the percentage of the charged capacity of a battery cell relative to the discharged capacity that appears when the battery cell is discharged from 4.6V to 2.0V is X.
[0025] The present inventors have conducted extensive research to improve the resistance and output characteristics of lithium secondary batteries using perlithium manganese oxides. As a result, they have found that by performing an activation process under specific charging conditions during the manufacture of a lithium secondary battery, it is possible to minimize cation mixing and oxygen desorption, thereby improving the positive electrode and cell resistance characteristics, and thus completed the present invention.
[0026] The present invention will be specifically described below.
[0027] <Lithium secondary battery> The lithium secondary battery according to the present invention includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a perlithium manganese-based oxide in which the manganese content in all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1.
[0028] In addition, in the lithium secondary battery according to the present invention, when a graph of voltage V vs. battery discharge capacity Q measured while charging to 4.6 V at 0.1 C and then discharging to 2.0 V at 0.1 C is differentiated, the discharge curve area in the voltage range of 2.0 V to 3.5 V is 35% or less, preferably 20% to 35%, when the total discharge curve area is 100% in a dQ / dV graph obtained by differentiating the graph of voltage V vs. battery discharge capacity Q measured while charging to 4.6 V at 0.1 C and then discharging to 2.0 V at 0.1 C.
[0029] It is known that the peak that appears at 3.5V or less during the discharge of a lithium secondary battery is a peak that appears due to the oxygen redox reaction and the redox reaction of Mn ions mixed with cations. That is, the larger the discharge curve area that appears at 3.5V or less, the more the oxygen redox reaction and the mixing of cations increases. On the other hand, if the oxygen redox reaction and the mixing of cations increase, the positive electrode resistance increases significantly and the output characteristics decrease. Therefore, in the present invention, the activation conditions during the manufacture of a lithium secondary battery are adjusted so that the discharge curve area that appears in the voltage range of 2.0V to 3.5V in the dQ / dV graph is 35% or less of the total discharge curve area, thereby suppressing the increase in the positive electrode resistance due to the mixing of cations. When the discharge curve area that appears in the voltage range of 2.0V to 3.5V in the dQ / dV graph satisfies 35% or less of the total discharge curve area, the resistance of the positive electrode and the cell is reduced, and excellent output characteristics can be achieved. However, if the discharge curve area in the voltage range of 2.0V to 3.5V is too small, the capacity characteristics may decrease. Therefore, it is more preferable that the area of the discharge curve appearing in the voltage range of 2.0V to 3.5V in the dQ / dV graph is about 20% to 35% of the total discharge curve area.
[0030] Each component of the lithium secondary battery according to the present invention will now be described in more detail.
[0031] positive electrode The positive electrode according to the present invention includes, as a positive electrode active material, a perlithium manganese-based oxide in which the manganese content in all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1. Specifically, the positive electrode of the present invention includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a perlithium manganese-based oxide in which the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1.
[0032] In the case of perlithium manganese oxides containing an excess of lithium, the layered phase (LiM'O 2 ) and rock salt phase (Li2 MnO 3 ) has a structure in which they are mixed, and in the initial activation process, while the rock salt phase is activated, an excessive amount of lithium ions are generated, and a high capacity can be realized.
[0033] Preferably, the over-lithium manganese-based oxide may be represented by Chemical Formula 1.
[0034] [Chemical Formula 1] Li a Ni b Co c Mn d M e O 2 In the above Chemical Formula 1, M may be at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0035] On the other hand, a is the molar ratio of Li in the over-lithium manganese-based oxide, and 1 < a, 1.1 ≤ a ≤ 1.5, or 1.1 ≤ a ≤ 1.3 may be satisfied. When a satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be sufficiently compensated, and high-capacity characteristics can be realized.
[0036] The b is the molar ratio of Ni in the over-lithium manganese-based oxide, and 0 ≤ b ≤ 0.5, 0.1 ≤ b ≤ 0.4, or 0.2 ≤ b ≤ 0.4 may be satisfied.
[0037] The c is the molar ratio of Co in the over-lithium manganese-based oxide, and 0 ≤ c ≤ 0.1, 0 ≤ c ≤ 0.08, or 0 ≤ c ≤ 0.05 may be satisfied. When c exceeds 0.1, it is difficult to ensure a high capacity, and gas generation and degradation of the positive electrode active material may be aggravated, resulting in a decrease in life characteristics.
[0038] The d is the molar ratio of Mn in the over-lithium manganese-based oxide, and 0.5 ≤ d < 1.0, 0.50 ≤ d ≤ 0.80, or 0.50 ≤ d ≤ 0.70 may be satisfied. When d is less than 0.5, the ratio of the rock salt phase is excessively small, and the negative electrode irreversible compensation and capacity improvement effects are negligible.
[0039] The e is a molar ratio of the doping element M in the lithium manganese oxide, and may be 0≦e≦0.2, 0≦e≦0.1, or 0≦e≦0.05. If the content of the doping element is too high, it may adversely affect the capacity of the active material.
[0040] Meanwhile, in the perlithium manganese oxide represented by [Chemical Formula 1], the molar ratio of Li to the total molar number of metal elements excluding Li (Li / Me) may be 1.2 to 1.5, 1.25 to 1.5, or 1.25 to 1.4. When the Li / Me ratio satisfies the above range, the rate characteristic and capacity characteristic are excellent. If the Li / Me ratio is too high, the electrical conductivity decreases and the rock salt phase (Li 2 MnO 3 ) may increase, resulting in a faster degradation rate, and if it is too low, the effect of improving the energy density is minimal.
[0041] Meanwhile, the composition of the lithium manganese oxide can also be expressed by the following [Chemical Formula 2]. [Chemical formula 2] X Li 2 MnO 3 ·(1-X)Li[Ni 1-y-z-w Mn y Co z M w ]O 2 In the above [Chemical Formula 2], M may be at least one selected from the group consisting of metal ions Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0042] The X is Li in the perlithium manganese oxide. 2 MnO 3 The ratio of the phases X may be 0.2≦X≦0.5, 0.25≦X≦0.5, or 0.25≦X≦0.4. 2 MnO 3When the phase ratio satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be sufficiently compensated for, and high capacity characteristics can be achieved.
[0043] The y is LiM'O 2 The molar ratio of Mn in the layered phase may be 0.4≦y<1, 0.4≦y≦0.8, or 0.4≦y≦0.7.
[0044] The z is LiM'O 2 The molar ratio of Co in the layered phase may be 0≦z≦0.1, 0≦z≦0.08, or 0≦z≦0.05. If z exceeds 0.1, gas generation and degradation of the positive electrode active material may be intensified, resulting in reduced life characteristics.
[0045] The w is LiM'O 2 The molar ratio of the doping element M in the layered phase may be 0≦w≦0.2, 0≦w≦0.1 or 0≦w≦0.05.
[0046] Meanwhile, the positive electrode active material according to the present invention may further include a coating layer on the surface of the perlithium manganese-based oxide, if necessary. When the positive electrode active material includes a coating layer, the coating layer inhibits contact between the perlithium manganese-based oxide and the electrolyte, thereby reducing electrolyte side reactions, thereby improving the life characteristics.
[0047] The coating layer is a coating element M 1 The coating element M 1 For example, the coating element M may be at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, and may be preferably Al, Co, Nb, W, and combinations thereof, and more preferably Al, Co, and combinations thereof. 1 may contain two or more kinds, for example, Al and Co.
[0048] The coating elements are in the oxide form in the coating layer, i.e., M 1 It can exist as Oz, where 1≦z≦4.
[0049] The coating layer may be formed by dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), etc. Among these, it is preferable to form the coating layer by atomic layer deposition, since it is possible to form the coating layer over a wide area.
[0050] The coating layer may have an area of 10 to 100%, preferably 30 to 100%, and more preferably 50 to 100% of the total surface area of the perlithium manganese oxide particles. When the coating layer has an area within the above range, the effect of improving the life characteristics is excellent.
[0051] Meanwhile, the positive electrode active material according to the present invention may be in the form of secondary particles in which a plurality of primary particles are aggregated, and the average particle diameter D 50 The diameter of the positive electrode active material may be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 4 μm to 8 μm. 50 When satisfies the above range, excellent electrode density can be achieved and deterioration of capacity and rate characteristics can be minimized.
[0052] The positive electrode active material has a BET specific surface area of 1 m 2 / g~10m 2 / g, 3-8m 2 / g or 4~6m 2 If the BET specific surface area of the positive electrode active material is too low, the reaction area with the electrolyte is insufficient, making it difficult to achieve sufficient capacity, whereas if the specific surface area is too high, moisture absorption is rapid, accelerating side reactions with the electrolyte, making it difficult to ensure life characteristics.
[0053] Meanwhile, the perlithium manganese oxide may be prepared by mixing a transition metal precursor and a lithium source material and then calcining the mixture.
[0054] The lithium source material may be, for example, a lithium-containing carbonate (e.g., lithium carbonate), a hydrate (e.g., lithium hydroxide hydrate (LiOH·H 2 O), hydroxides (e.g., lithium hydroxide), nitrates (e.g., lithium nitrate (LiNO 3 and the like), chlorides (for example, lithium chloride (LiCl) and the like), and any one of these can be used alone or a mixture of two or more of them can be used.
[0055] Meanwhile, the transition metal precursor may be in the form of a hydroxide, oxide, or carbonate. When a precursor in the form of a carbonate is used, it is more preferable in that a positive electrode active material having a relatively high specific surface area can be prepared.
[0056] The transition metal precursor may be prepared through a co-precipitation process. For example, the transition metal precursor may be prepared by dissolving each transition metal-containing raw material in a solvent to prepare a metal solution, mixing the metal solution, an ammonium cation complexing agent, and a basic compound, and then performing a co-precipitation reaction. If necessary, an oxidizing agent or oxygen gas may be further added during the co-precipitation reaction.
[0057] In this case, the transition metal-containing raw material may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, etc. of each transition metal. Specifically, the transition metal-containing raw material may be NiO, NiCO 3 2Ni(OH) 2 4H 2 O, NiC 2 O 2 2H 2 O, Ni(NO 3 ) 2 6H 2 O, NiSO 4 , NiSO 4 6H 2 O, Mn 2 O 3 , MnO 2 , Mn 3 O 4 MnCO 3 , Mn(NO3 ) 2 , MnSO 4 H 2 O, manganese acetate, manganese halides, cobalt oxide, cobalt carbonate, cobalt sulfate, cobalt acetate, cobalt halides, and the like.
[0058] The ammonium cation complexing agent is NH 4 OH, (NH 4 ) 2 SO 4 , N.H. 4 NO 3 , N.H. 4 Cl, CH 3 COONH 4 , and N.H. 4 CO 3 The present invention may be at least one selected from the group consisting of:
[0059] The basic compound is NaOH, Na 2 CO 3 , KOH, and Ca(OH) 2 The form of the precursor may vary depending on the type of basic compound used. For example, when NaOH is used as the basic compound, a precursor in the form of hydroxide can be obtained; 2 CO 3 When a basic compound and an oxidizing agent are used together, a precursor in the form of an oxide can be obtained.
[0060] Meanwhile, the transition metal precursor and the lithium source material may be mixed in amounts such that the total transition metal (Ni+Co+Mn):Li molar ratio is 1:1.05 to 1:2, preferably 1:1.1 to 1:1.8, and more preferably 1:1.25 to 1:1.8.
[0061] Meanwhile, the firing may be carried out at a temperature of 600° C. to 1000° C. or 700° C. to 950° C., and the firing time may be 5 hours to 30 hours or 5 hours to 20 hours. The firing atmosphere may be an air atmosphere or an oxygen atmosphere, for example, an atmosphere containing 20 to 100 volume % of oxygen.
[0062] Meanwhile, the positive electrode active material layer may further include a conductive material and a binder in addition to the positive electrode active material.
[0063] Examples of the conductive material include spherical or scaly graphite; carbonaceous materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotubes, and multi-walled carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and any one of these may be used alone or in combination. The conductive material may be included in an amount of 0.1 to 20 wt%, 1 to 20 wt%, or 1 to 10 wt%, based on the total weight of the positive electrode active material layer.
[0064] Examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these can be used alone or in combination. The binder may be included in an amount of 1 to 20% by weight, 2 to 20% by weight, or 2 to 10% by weight based on the total weight of the positive electrode active material layer.
[0065] negative electrode The negative electrode may include, for example, a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, and optionally a binder and a conductive material.
[0066] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 to 500 μm, and like the positive electrode current collector, the surface of the current collector can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0067] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), SnO 2 , metal oxides capable of doping and dedoping lithium, such as vanadium oxide and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these can be used.
[0068] Also, a metallic lithium thin film may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, flaky, spherical, or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0069] The conductive material is used to give conductivity to the electrode, and can be used without any particular restrictions as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material may be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0070] The binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these can be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0071] For example, the negative electrode active material layer may be prepared by coating a negative electrode slurry containing a negative electrode active material, and optionally a binder and a conductive material, on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry on a separate support and then peeling the negative electrode slurry from the support to obtain a film, which may then be laminated on the negative electrode current collector.
[0072] separation membrane The lithium secondary battery according to the present invention may further include a separator interposed between the positive and negative electrodes. The separator separates the negative and positive electrodes to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular restrictions. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability may be used. Specifically, a porous polymer film may be used, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. In addition, a conventional porous nonwoven fabric may be used, for example, a nonwoven fabric made of a high-melting point glass fiber, polyethylene terephthalate fiber, or the like. In addition, a coated separator containing a ceramic component or a polymeric material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.
[0073] electrolyte The electrolyte may be any of various electrolytes that can be used in lithium secondary batteries, such as an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, or a combination thereof, and is not particularly limited in type.
[0074] For example, the electrolyte can include an organic solvent and a lithium salt.
[0075] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran, etc.; a ketone solvent such as cyclohexanone, etc.; an aromatic hydrocarbon solvent such as benzene or fluorobenzene, etc.; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate), etc. Examples of solvents that can be used include carbonate solvents such as polycarbonate (PC); alcohol solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes.
[0076] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt is F - , Cl - , Br - , I - , NO 3 - , N(CN) 2 - , B.F. 4, C.F. 3 CF 2 SO 3 - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , C.F. 3 CF 2 (CF 3 ) 2 CO - , (CF 3 SO 2 ) 2 CH - ,(SCIENCE FICTION 5 ) 3 C - , (CF 3 SO 2 ) 3 C - , C.F. 3 (CF 2 ) 7 SO 3 - , C.F. 3 CO 2 - , C.H. 3 CO 2 - , SCN - , and (CF 3 CF 2 SO 2 ) 2 N - and the lithium salt may be at least one selected from the group consisting of LiPF 6 , LiN(FSO 2 ) 2 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 )2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 5.0M.
[0077] In addition to the above components, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, and improving the discharge capacity of the battery. For example, the additives may be haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination, but are not limited thereto. The additives may be included in an amount of 0.1 to 10 wt %, preferably 0.1 to 5 wt %, based on the total weight of the electrolyte.
[0078] <Method of manufacturing lithium secondary battery> Next, a method for producing a lithium secondary battery according to the present invention will be described.
[0079] The method for manufacturing a lithium secondary battery according to the present invention includes: (1) a step of preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte; and (2) a step of activating the battery cell, wherein the activation step includes a first charging step of charging the battery cell at a C-rate of less than 0.5 C; and a second charging step of charging the battery cell at a C-rate of 0.5 C or more.
[0080] (1) Preparing the battery cells First, a battery cell including a positive electrode, a negative electrode, and an electrolyte is prepared.
[0081] The battery cell may be manufactured by, for example, forming an electrode assembly including a positive electrode and a negative electrode, housing the electrode assembly in a battery case, injecting an electrolyte, and sealing the battery case. In this case, the electrode assembly may include a separator between the positive electrode and the negative electrode.
[0082] The positive electrode, the negative electrode, the separator, and the electrolyte are the same as those described above, and therefore a detailed description thereof will be omitted.
[0083] Meanwhile, the electrode assembly may be an electrode assembly of various types well known in the art, for example, a jelly roll type, a stack type, a stack and lamination type, or a stack and folding type, and the type is not particularly limited.
[0084] The jelly roll type electrode assembly can be manufactured by interposing a sheet-shaped separator between a sheet-shaped positive electrode and a sheet-shaped negative electrode, and then winding the electrodes in one direction.
[0085] The stack-type electrode assembly may be manufactured by cutting a positive electrode, a separator, and a negative electrode into a desired shape, and then stacking the cut positive electrode / separator / negative electrode in sequence.
[0086] The stack-and-lamination type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, stacking the plurality of unit cells with a separator interposed therebetween, and laminating the stacked unit cells by a method such as heating.
[0087] The stack-and-fold type electrode assembly may be manufactured by stacking a positive electrode, a separator, and a negative electrode to manufacture a plurality of unit cells, arranging the plurality of unit cells on one or both sides of a long folding separator, and then winding up the folding separator.
[0088] Meanwhile, the battery case may be any of various battery cases known in the art, such as a cylindrical battery case, a square battery case, or a pouch-type battery case, and the type is not particularly limited.
[0089] (2) Activation stage Next, an activation step is performed in which the battery cell is charged and discharged at least once to electrically activate the battery. The activation step is a process in which the battery cell is charged and discharged to impart electrical characteristics and a solid electrolyte interphase (SEI) film is formed on the electrodes to stabilize the battery.
[0090] In the present invention, the charging in the activation process is performed in two or more stages with different rate limiting steps, thereby forming a robust SEI film on the electrode and simultaneously minimizing the occurrence of oxygen desorption and cation mixing during the activation process.
[0091] Specifically, the charging includes a first charging stage in which the battery cells are charged at a C-rate less than 0.5C; and a second charging stage in which the battery cells are charged at a C-rate equal to or greater than 0.5C.
[0092] The first charging step is performed at a rate (C-rate) of less than 0.5 C, preferably 0.05 C to less than 0.5 C. If the current rate is fast, 0.5 C or more, during the first charging step, an SEI film may be formed unstably on the electrode surface. If an SEI film is formed unstably on the electrode surface, the SEI film may be easily decomposed during battery operation, causing rapid deterioration of the electrode, which may result in a significant decrease in life characteristics.
[0093] Meanwhile, the first charging step is preferably performed from an SOC of 0 of the battery cell until the SOC reaches 10 to 40. When the charge capacity in the first charging step satisfies the above range, a strong and dense SEI film is formed on the electrode surface, thereby achieving excellent life characteristics.
[0094] Meanwhile, the first charging step can be performed in two or more steps with different rate limits, if necessary. For example, the first charging step can include a 1-1 charging step in which the battery cell is charged at a C-rate of 0.1 to less than 0.3C, and a 1-2 charging step in which the battery cell is charged at a C-rate higher than the C-rate of the 1-1 charging step and less than 0.5C. In this case, the 1-1 charging step is performed from SOC 0 to SOC 3 to 5, and the 1-2 charging step is performed from SOC 3 to 5 to SOC 10 to 40. When the first charging step is performed in two steps as described above, the current rate at the beginning of the formation of the SEI film can be maintained lower, and a stronger and denser SEI film can be formed.
[0095] Meanwhile, the first charging step can be performed in a constant current mode (CC mode).
[0096] Then, the second charging step is performed at a C-rate of 0.5 C or more, preferably 0.5 C to 2 C. When the second charging step is performed at a C-rate of 0.5 C or more, the Li 2 MnO 3 The activation of the monoclinic phase is reduced, which suppresses oxygen desorption and cation mixing during the activation process. In addition, by performing the second charging step at a relatively fast C-rate, the time required for the activation process is reduced, thereby shortening the battery production time.
[0097] Meanwhile, the second charging step is preferably performed after the first charging step, that is, until the SOC of the battery cell reaches from 10-40 to 90-150. When the charging capacity in the second charging step satisfies the above range, the SEI film can be prevented from being incompletely formed, and oxygen desorption and mixed generation of cations during the activation process can be reduced, thereby minimizing an increase in the positive electrode resistance.
[0098] The second charging step can be performed in a constant current mode (CC mode) or a constant current-constant voltage mode (CC-CV mode).
[0099] In the second charging step, the charge cut-off voltage may be 4.4 V or more, for example, 4.4 V to 4.8 V or 4.5 V to 4.7 V. When the charge cut-off voltage in the second charging step satisfies the above range, the perlithium manganese oxide is activated and high capacity characteristics can be achieved.
[0100] Next, the battery cell charged through the first and second charging steps is discharged. At this time, the discharge can be performed at a C-rate of 0.1 C to 1 C, preferably 0.3 C to 1 C. When the discharge rate satisfies the above range, it is possible to obtain an effect of shortening the activation process time.
[0101] On the other hand, the discharge can be carried out in a constant current mode (CC mode).
[0102] On the other hand, the discharge cut-off voltage may be 2.0V to 3.0V.
[0103] Preferably, in the present invention, the charging and discharging in the activation step can be carried out in a voltage range of 2.0V to 4.6V.
[0104] Meanwhile, the activation process is preferably carried out at a temperature of 25° C. to 55° C., and more preferably 30° C. to 45° C. When the activation process is carried out within this temperature range, the activation is smoothly carried out even at a relatively high C-rate. If the activation temperature is too low, the lithium ion mobility decreases and the activation may not be smoothly carried out, whereas if the activation temperature is too high, the elution of transition metals such as manganese may occur.
[0105] Furthermore, the activation process may be performed under pressurized conditions, if necessary. The pressurization may be performed by mounting the battery cell in a jig and applying pressure to the battery cell through the jig. When the activation process is performed under pressurized conditions, it is advantageous in that gas generated during the activation process can be easily discharged.
[0106] Meanwhile, although not essential, if necessary, the activation step may further include an aging step, which is for the purpose of uniformly impregnating the electrolyte into the electrode assembly and stabilizing the battery, and may be performed before charging, during charging, and / or after discharging, and may be performed one or more times.
[0107] The aging step can be carried out at a temperature of, for example, 20° C. to 60° C., preferably 20° C. to 50° C., and more preferably 30° C. to 50° C. When the aging is carried out at the above temperature, the electrolyte impregnation and lithium mobility are improved, and activation is carried out more smoothly.
[0108] The lithium secondary battery manufactured through the activation process may have a discharge curve area of 35% or less, preferably 20% to 35%, in a voltage range of 2.0 to 3.5 V, when the total discharge curve area is 100% in a dQ / dV graph obtained by differentiating a graph of voltage V vs. battery discharge capacity Q measured while charging to 4.6 V at 0.1 C and then discharging to 2.0 V at 0.1 C.
[0109] The present invention will be described in more detail with reference to the following specific examples. EXAMPLES
[0110] Example 1 The positive electrode active material, conductive material, and PVDF binder were mixed in a weight ratio of 96:1.5:2.5 in N-methylpyrrolidone to prepare a positive electrode slurry. 2 MnO 3 ·0.65Li[Ni 0.595 Co 0.005 Mn 0.4 ]O 2 The positive electrode slurry was applied onto an aluminum current collector sheet, dried, and then rolled to prepare a positive electrode.
[0111] Anode active material:conductive material:binder were mixed in water in a weight ratio of 97:1:2 to prepare anode slurry. Graphite was used as the anode active material, carbon black as the conductive material, and a mixture of SBR (styrene-butadiene) and carboxymethyl cellulose (CMC) was used as the binder. The anode slurry was applied onto a copper current collector sheet, dried, and then rolled to prepare anode.
[0112] An electrode assembly was prepared by interposing a separator between the positive and negative electrodes prepared as described above, and the electrode assembly was inserted into a battery case, and an electrolyte was then injected to prepare a battery cell.
[0113] The battery cell was charged at 45° C. in constant current mode at 0.2 C to SOC 3 (1-1 charging stage), charged at constant current mode at 0.3 C to SOC 30 (1-2 charging stage), charged at constant current mode at 0.5 C to 4.6 V (2nd charging stage), and then discharged at a constant current of 0.5 C to 2.0 V to perform an activation process, thereby producing a lithium secondary battery.
[0114] Example 2 A lithium secondary battery was manufactured in the same manner as in Example 1, except that charging was performed at 1.0 C in the second charging step.
[0115] Example 3 A lithium secondary battery was manufactured in the same manner as in Example 1, except that charging was performed at 1.5 C in the second charging step.
[0116] Comparative Example 1 A lithium secondary battery was manufactured in the same manner as in Example 1, except that the second charging step was performed in a constant current-constant voltage mode (0.05C CV-cut) of 0.3C.
[0117] Experimental Example 1 The secondary batteries manufactured in the examples and comparative examples were charged to 4.60V at 25°C in a constant current-constant voltage mode of 0.1C (CC-CV mode, CV mode cut-off condition: 0.05C) and discharged to 2.0V at a constant current of 0.1C to measure a voltage-discharge capacity graph, and the voltage-capacity graph was differentiated to obtain a dQ / dV graph. The measured dQ / dV graph is shown in FIG. 1. In addition, the percentage of the discharge curve area in the 2V to 3.5V region to the total discharge curve area (i.e., the discharge curve area in the 2.0 to 4.6V region) is shown in Table 1 below.
[0118] [Table 1]
[0119] As shown in Table 1 and FIG. 1, the lithium secondary batteries of Examples 1 to 3, which were manufactured by performing the second charge at a rate of 0.5C or more in the activation process, showed a discharge curve area in the 2V to 3.5V region of 35% or less of the total discharge curve area, while the lithium secondary battery of Comparative Example 1, which was performed the second charge at a rate of 0.3C, showed a discharge curve area in the 2V to 3.5V region of more than 40%.
[0120] Experimental Example 2 A three-electrode cell (reference electrode: LTO) was prepared using each of the positive electrodes prepared in Examples 1 to 3 and Comparative Example 1 as a working electrode, and the three-electrode cell was subjected to EIS (Electrochemical Impedance Spectroscopy) analysis and DCIR (Direct Current Internal Resistance) analysis to measure the positive electrode resistance.
[0121] The EIS analysis results are shown in Figure 2, and the DCIR analysis results are shown in Figure 3.
[0122] 2, it can be seen that the lithium secondary batteries of Examples 1 to 3 have lower impedance values than the lithium secondary battery of Comparative Example 1, and the frequency (Hz) at which the impedance is exhibited is also increased, showing that the kinetics of the resistance response is also improved.
[0123] Also, it can be seen from FIG. 3 that the lithium secondary batteries of Examples 1 to 3 have lower internal resistance than the lithium secondary battery of Comparative Example 1.
Claims
1. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, the positive electrode and the negative electrode comprising a perlithium manganese-based oxide in which the manganese content in all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1; The lithium secondary battery is charged to 4.6 V at 0.1 C and then discharged to 2.0 V at 0.1 C. In a dQ / dV graph obtained by differentiating a graph of voltage V and battery discharge capacity Q measured while charging the lithium secondary battery to 4.6 V at 0.1 C, when the total discharge curve area is 100%, the discharge curve area in the voltage range of 2.0 to 3.5 V is 35% or less.
2. 2. The lithium secondary battery according to claim 1, wherein a discharge curve area in the voltage range of 2.0 to 3.5 V is 20% to 35% or less.
3. 2. The lithium secondary battery of claim 1, wherein the perlithium manganese oxide is represented by the following formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M e O 2 In the above formula 1, 1<a, 0≦b≦0.5, 0≦c≦0.1, 0.5≦d<1.0, 0≦e≦0.2, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
4. 4. The lithium secondary battery according to claim 3, wherein, in Chemical Formula 1, 1.1≦a≦1.5, 0.1≦b≦0.4, 0≦c≦0.05, 0.5≦d≦0.80, and 0≦e≦0.
1.
5. preparing a battery cell including a positive electrode, a negative electrode, and an electrolyte, the positive electrode including a perlithium manganese-based oxide in which the manganese content in all metals excluding lithium exceeds 50 mol % and the ratio of the number of moles of lithium to the number of moles of all metals excluding lithium (Li / Me) exceeds 1; and Activating the battery cell by charging and discharging the battery cell at least once; The activation step includes a first charging step of charging the battery cell at a C-rate of less than 0.5 C, and a second charging step of charging the battery cell at a C-rate of 0.5 C or more.
6. The method for manufacturing a lithium secondary battery according to claim 5, wherein the perlithium manganese-based oxide is represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M e O 2 In the above formula 1, 1<a, 0≦b≦0.5, 0≦c≦0.1, 0.5≦d<1.0, 0≦e≦0.2, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
7. 7. The method of claim 5, wherein the first charging step is performed until the SOC of the battery cell is 10 to 40, and the second charging step is performed after the first charging step until the SOC of the battery cell is 90 to 150.
8. The method of claim 5, wherein the first charging step and the second charging step are performed in a constant current mode (CC mode).
9. 6. The method of claim 5, wherein the first charging step is performed in a constant current mode (CC mode), and the second charging step is performed in a constant current-constant voltage mode (CC-CV mode).
10. 6. The method for manufacturing a lithium secondary battery according to claim 5, wherein an end-of-charge voltage in the second charging stage is 4.4 V or more.
11. The method for producing a lithium secondary battery according to claim 5, wherein the charging and discharging are performed in a voltage range of 2.0 V to 4.6 V.
12. 6. The method for manufacturing a lithium secondary battery according to claim 5, wherein a graph of voltage V vs. battery discharge capacity Q measured while charging the lithium secondary battery to 4.6 V at 0.1 C and then discharging the lithium secondary battery to 2.0 V at 0.1 C is differentiated to obtain a dQ / dV graph, in which a discharge curve area in a voltage range of 2.0 to 3.5 V is 35% or less when a total discharge curve area is 100%.
Citation Information
Patent Citations
Air filter
KR102782617B1